2019
DOI: 10.1177/1461444819829873
|View full text |Cite
|
Sign up to set email alerts
|

Embodied well-being through two media technologies: Virtual reality and social media

Abstract: How the body is perceived through media is key to many well-being interventions. Researchers have examined the effects of platforms on users’ self-perceptions, including immersive virtual reality, nonimmersive virtual worlds, and social media such as Facebook. In this article, we use several conceptions of levels of embodiment to compare empirical work on the effects of virtual reality and social media as they relate to perceptions and conceptions of the self and body. We encourage social media researchers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 91 publications
0
13
0
2
Order By: Relevance
“…A growing body of research is revealing that a user's simulated body can significantly alter perceptions of identity and environment [136][137][138]. As mentioned above, investigations of these altered perceptions aim at enhancing understanding of virtual embodiment in various therapies [139], wellbeing applications [140], and investigations into the ways in which the brain maps the body schema onto a virtual object to create an illusion of ownership. For example, experimental paradigms such as the "body swap" [141] and the "rubber hand" illusions [142] have been developed.…”
Section: Social Xr With Virtual Humansmentioning
confidence: 99%
“…A growing body of research is revealing that a user's simulated body can significantly alter perceptions of identity and environment [136][137][138]. As mentioned above, investigations of these altered perceptions aim at enhancing understanding of virtual embodiment in various therapies [139], wellbeing applications [140], and investigations into the ways in which the brain maps the body schema onto a virtual object to create an illusion of ownership. For example, experimental paradigms such as the "body swap" [141] and the "rubber hand" illusions [142] have been developed.…”
Section: Social Xr With Virtual Humansmentioning
confidence: 99%
“…Many models of embodiment describe the self as ''an integration of a social or conceptual self along with our physical self.'' 5 In other words, humans understand themselves through both their interactions with others and their interactions with the environment.…”
Section: What Is Embodiment?mentioning
confidence: 99%
“…Scientists have found that this sense of self can be manipulated by creating conflicts in visual and tactile cues, creating a ''body illusion.'' 5 These illusions can either arise organically through an issue with a person's sense of embodiment created by their own mind, or they can be created artificially, such as during therapy in an effort to encourage the brain to reassess and update sensory organization to correct the induced conflict, 5 essentially ''rebooting'' a person's embodiment.…”
Section: What Is Embodiment?mentioning
confidence: 99%
“…We define well-being as the opposite of cybersickness, with cybersickness being the physical discomfort resulting from use of the immersive system, obstructing the user from accurately performing the task at hand. Note that our definition of wellbeing slightly differs from the one common in literature, as ours focuses on the effects on the user during playback of the immersive experience while the term in literature mostly refers to the long-term effects of repeated exposure to these kinds of experiences [12]. Well-being could be measured by means of questionnaires prior and subsequent to the experiment, in which different aspects of (cyber)sickness such as dizziness, blurred vision, decreased concentration, headache etc.…”
Section: Subjective Evaluations: From Rating Visualmentioning
confidence: 99%